Peran Kepala Sekolah dan Yayasan dalam Mengembangkan Lembaga Pendidikan Islam - Ilma, Zaida Fithrotul; Hariyati, Nunuk; Riyanto, Yatim (Ideas Publishing, 2024)
This article discusses the role of school principals and foundations in developing Islamic educational institutions, focusing on the quality of education and leadership. This study aims to provide an overview of the role that must be performed by school principals and foundations in developing Islamic educational institutions. A literature study is used to present the picture. The results showed that the principal must have managerial abilities, while the foundation plays a role in setting policies and motivating the team. The implication of this research is the importance of adequate understanding, experience, and knowledge for school principals and foundation chairmen in developing Islamic educational institutions